Environmental health risks perception, attitude, and avoidance behaviour toward municipal solid waste incinerator. Issue 2 (4th March 2018) - Lin, Ping-Yi; Lai, Shu-Ping; Wang, Min-Chao; Liang, Jeng-Jong; Chiang, Chow-Feng; Kuo, Hsien-Wen
ABSTRACT: This study aims to assess the relationship between risk perception, attitude, and avoidance among residents toward an urban incinerator in Taichung, Taiwan. A cross-sectional study was conducted and three schools were enrolled. The case group was composed of 514 residents who live near an incinerator. The control group was composed of 264 people nearly the same age and who have lived in that area basically the same period of time. All participants were interviewed using a structured questionnaire. Results of this study showed that there was no significant difference between the exposure group and the control group in risk perception and attitude regarding the incinerator. However, the exposure group showed a significantly higher desire to move within one year or move sometime in the future than the control group. Therefore, these people should encourage the Environmental Protection Administration (EPA) to do everything it can to make sure that the incinerator operates safely.